Quaternary PAMAM-based antibacterial polyurethane foam - Yivlik, Yusuf; Taylanli, Bahar; Tulu, Metin; Mucahit Guncu, Mehmet; Aksu, Burak; Yapaoz, Melda Altikatoglu; Eren, Tarik (TAYLOR & FRANCIS INC, 2025)
Microbial colonization of surfaces is a major cause of healthcare-associated infections, resulting in significant health and economic burdens. This study reports the design and synthesis of quaternary poly(amidoamine) (PAMAM)-based cationic dendrons (QD-PAMAM-A and QOD-PAMAM-A) and their incorporation into polyurethane (PU) foams to generate non-leaching, contact-active antibacterial materials. The dendrons were synthesized via end-capping PAMAM (0.5 generation) with dimethylaminopropylamine, followed by quaternization with bromoalkyls. The resulting dendrons were covalently incorporated into PU foam matrices, with and without AgNO3, to explore synergistic antibacterial effects. Structural confirmation was achieved by Fourier transform infrared, 1H/1(3)C nuclear magnetic resonance and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) analysis, while the thermal and mechanical properties of the foams were evaluated by thermogravimetric analysis, compressive strength testing and density measurements. Scanning electron microscopy and energy-dispersive X-ray spectroscopy confirmed homogeneous Ag distribution in the PU matrix. Antibacterial activity was tested against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli. PU foams containing 15 wt% QD-PAMAM-A exhibited 100% killing efficiency against S. aureus but incomplete inhibition of E. coli. The addition of AgNO3 resulted in the complete eradication of both bacterial strains, demonstrating a synergistic effect between cationic dendrons and silver ions. Mechanical testing indicated a significant reinforcement effect of AgNO3, increasing compressive strength by more than 50% compared to unmodified PU. These results suggest that QD-PAMAM-A/Ag hybrid PU foams are promising candidates for antimicrobial applications in healthcare, water treatment and surface protection. In addition to its biocidal activity, the catalytic efficiency of quaternary PAMAM in the PU foam matrix was also investigated.
Keywords: Dendrimer; antibacterial; silver nitrate; polyurethane foam; quaternary ammonium; ANTIMICROBIAL ACTIVITY; SURFACES; COATINGS; Polymer Science